Indigenous knowledge and socio-economic significance of Enset (Ensete ventricosum (Welw.) Cheeseman) cultivation and food processing in Sidama, Southern Ethiopia - G. Egziabher, Yemane; Kebede, Firew; Kassahun Mengistu, Dejene; Tadesse, Haile Kiros; Mahari, Milete; Welday, Yemane (Ethnobotany Research and Applications, 2020)
Background: Peoples’ culture and natural resources tie has first line survival value in Ethiopia. The drought resistant crop locally called enset supports about 20 million populations. The aim of this research is to investigate the farmer’s indigenous knowledge in cultivation, food processing and use value of enset in Sidama, southern Ethiopia. Methods: The research was undertaken in Hula district in March and May 2017. The study area is predominantly enset growing highland ranging from2100-3200 masl. Focus group discussion with key informants and interview with development agents were used to collect data in six kebelles. For enset landraces survey about 13 households backyard were randomly visited and the result was concretized with field observation. Results: A total of 26 landraces were recorded and farmers identify enset landrace using combinations of agro-morphological traits. Utilitarian and cultural values are the main determining factors for the maintenance and conservation of large number of landraces. Majority (80%) of the people are dependent on kocho-bulla and Amicho for food and suckers for income. The farmers’ indigenous knowledge in selection and maintenance of enset landrace diversity is powerful; environmental stresses and selection are the main causes for the loss of some landraces. Conclusion: There is strong link between the community and the diverse landraces of enset in the study area. Food processing from enset is laborious, hence demands technological innovation that ease job and maintains food quality. The use of suckers as means of reproduction helped to maintain the quality existed but adaptation to changing climate is low and seed utilization must be encouraged during in-situ conservation. Key words: Enset, indigenous knowledge, landrace diversity, Sidama